2015
DOI: 10.1177/0885066615592851
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Microbiology of Sepsis Syndromes in a University-Affiliated Urban Teaching Hospital and Level-1 Trauma and Burn Center

Abstract: Hospital mortality and hospital LOS of sepsis are similar to those reported in other observational studies. Our study confirms a decline in the mortality of sepsis predicted by earlier longitudinal studies and should prompt a resurgence of epidemiological research of the sepsis syndromes in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
5
13
0
Order By: Relevance
“…A 2009 report from investigators at Massachusetts General Hospital analyzing 2,039,776 admissions from the Nationwide Inpatient Sample, the largest in-patient dataset available in the United States, indicated that severe sepsis has increased following elective surgery from 0.3% to 0.9% [3]. Although in- hospital mortality rates declined from 44 to 34% during the 10 year interval, postoperative and post- injury sepsis continue to impose significant disease burden, costs and high death rates despite advances in care and newer antibiotics [3,4]. Across virtually all surgical injuries (major surgical intervention, trauma, burns) the majority of sepsis- related deaths have now shifted to occur late in the course of hospitalization and have been shown to be associated with immune-suppression and multi- drug resistant pathogens [59].…”
Section: Sepsis Incidence and Severity Is Increasing Among Surgical Pmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2009 report from investigators at Massachusetts General Hospital analyzing 2,039,776 admissions from the Nationwide Inpatient Sample, the largest in-patient dataset available in the United States, indicated that severe sepsis has increased following elective surgery from 0.3% to 0.9% [3]. Although in- hospital mortality rates declined from 44 to 34% during the 10 year interval, postoperative and post- injury sepsis continue to impose significant disease burden, costs and high death rates despite advances in care and newer antibiotics [3,4]. Across virtually all surgical injuries (major surgical intervention, trauma, burns) the majority of sepsis- related deaths have now shifted to occur late in the course of hospitalization and have been shown to be associated with immune-suppression and multi- drug resistant pathogens [59].…”
Section: Sepsis Incidence and Severity Is Increasing Among Surgical Pmentioning
confidence: 99%
“…In this clinical scenario, the pathogenesis of infection- related sepsis is framed as a simple matter of an exhausted immune system unable to contain a given microbial burden [11]. Yet microbial burden is often imprecisely characterized and defined primarily by the isolation of a given pathogen cultured from a site that is considered to be normally sterile (lung, urine, central line, blood) that contemporaneously correlates with the onset of sepsis and progressive organ failure [4]. This definition falls short in establishing the causality between the originally identified pathogen and the progression or resolution of the septic response [12].…”
Section: Sepsis Incidence and Severity Is Increasing Among Surgical Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-based therapies present a novel opportunity to improve trauma and critical care at both the acute and chronic phases that often follow injury. Although this field is still in its infancy, animal and human studies suggest that stem cells may hold great promise for the treatment of brain and spinal cord injuries, organ injuries, and extremity injuries such as those caused by orthopedic trauma, burns, and critical limb ischemia [19]. Barriers in the translation of cell therapies that include regulatory obstacles, challenges in manufacturing and clinical trial design, and a lack of funding are critical areas in need of development.…”
Section: Traumamentioning
confidence: 99%
“…In 2015, the Department of Defense Combat Casualty Care Research Program held a joint military-civilian meeting as part of its effort to inform the research community about this field and allow for effective planning and programmatic decisions regarding research and development. The objective of this article was to provide a "state of the science" review regarding cellular therapies in trauma and critical care, and to provide a foundation from which the potential of this emerging field can be harnessed to mitigate outcomes in critically ill trauma patients [19].…”
Section: Traumamentioning
confidence: 99%